Pocket dictionary of the Reformed tradition - Kapic, Kelly M., 1972-; Vander Lugt, Wesley, 1981- (Downers Grove, Illinois : IVP Academic, 2013)
Beginning to study Reformed theology is like stepping into a family conversation that has been going on for five hundred years. How do you find your bearings and figure out how to take part in this conversation? The Pocket Dictionary of the Reformed Tradition takes on this rich, boisterous and varied tradition in its broad contours, filling you in on its common affirmations and its particular dialect as well as its family tensions. -- Back Cover.
Includes bibliographical references (pages 135-140).
Description based on print version record.
Keywords: Reformed Church -- Dictionaries; Reformed Church; RELIGION / Christianity / Protestant; Dictionaries; Electronic books